Listeria Inactivation by the Combination of High Hydrostatic Pressure and Lactocin AL705 on Cured-Cooked Pork Loin Slices - Dallagnol, Andrea Micaela (2017)
The effect of the bacteriocin lactocin AL705 in combination with high hydrostatic pressure (HHP) on the inactivation of Listeria innocua 7, a nonpathogenic indicator for Listeria monocytogenes, deliberately inoculated (ca. 6.4 log CFU/g) onto the surface of ready-to-eat (RTE) sliced cured-cooked pork loin, was evaluated. Nontreated pork slices (control) and treatments subjected to lactocin AL705 (105 AU/ml) and/or HHP (400 or 600 MPa) were prepared. L. innocua 7 was monitored at days 1, 20, and 40 of storage at 4 °C. The results showed a complete inhibition of L. innocua 7 after the combined treatment with lactocin AL705 and 600 MPa and no regrowing of cells up to 40-day storage. The treatment at 600 MPa alone was not enough to avoid regrowth of L. innocua. Ultrastructural cell damage was observed at the cytoplasm and cell membrane/wall levels with all treatments; however, complete cell lysis was observed only with the combined treatment. HHP in combination with lactocin AL705 provided a wider margin of safety as post-processing listericidal treatment of RTE cured-cooked meat products.